Kajian Kitab Maqal Fi Al-Insan: Dirasah Qur’aniyah Karya ‘A>Ishah Bint Shati’ - Munaji Munaji; Shohebul Hajad (STAI Al-Mujtama Pamekasan, 2022)
Among the many commentators who tried to launch a new interpretation model from their predecessors was Bint Shati' who was known for his studies of literature and interpretation of the Qur'an. Among his works, Maqal Fi Al-Insan: Dirasah Qur'aniyyah, this book is a book that applies mawdhu'i interpretation with the interpretation method initiated by the author himself, namely Bint Shati' with the object of his discussion about humans in the perspective of the Qur'an. 'an. From the contents of this book, it can be understood that there are no synonyms in the Qur'an, so that all the vocabulary of the Qur'an which refers to human meanings have their respective meaning entities. Humans as a descendant of Adam are referred to as al-Nas. All humans have a very identical resemblance in al-bashar, and he is a different being from al-jinn as al-ins. Key words: al-insan, felt, Qur'aniyah, Bint Shati'